Dual-Task Performance in Older Adults With and Without Idiopathic Normal Pressure Hydrocephalus - Lilja-Lund, Otto; Nyberg, Lars; Maripuu, Martin; Laurell, Katarina (Frontiers in Aging Neuroscience, 2022)
Two of the main features of idiopathic normal pressure hydrocephalus (iNPH) are disturbed gait and cognition. These features are typically investigated separately, but here we combined walking with a cognitive task to investigate if older adults with iNPH were more susceptible to dual-task interference on walking than those without iNPH. In total, 95 individuals from the general population participated in our study. Of these, 20 were classified as Possible iNPH (median [interquartile range, IQR] 80 years [75–82.5]) and 75 as Unlikely iNPH (74 years [72–78]). Conversation, 10-m walking, semantic and phonemic verbal fluency were performed either combined or independently. “Stopping walking while talking” was noted. Pairwise comparisons and multiple logistic regression analyses were used. We found that the Possible iNPH group was older, stopped walking more frequently during the conversation, and had a slower single-task pace. The dual-task pace was slower for both groups. Only single-task walking pace could predict Possible iNPH when adjusted for age. We could establish a dual-task cost on gait performance in this sample of older adults from the general population, but the cost was not exclusive for individuals with Possible iNPH. To further assess the value of dual-task testing in iNPH, including observations of stopping walking while talking, a study of a clinical iNPH material with more severe symptoms would be valuable.